Keabsahan Perdamaian Kedua oleh Debitor Pailit dalam Proses Penundaan Kewajiban Pembayaran Utang (PKPU) - Achmad Sidik Jamaludin; Friedmus Imanuel Francis; Joko Kuncoro Adi; Alif Azis Assyadili (LPPM Universitas Ekasakti Padang, 2023)
Article 292 of the Law of the Republic of Indonesia Number 37 of 2004 concerning Bankruptcy and Suspension of Obligations for Payment of Debt stipulates that reconciliation cannot be resubmitted by the debtor. Case in Decision Number 59/Pdt.Sus-PKPU/2019/PN.Niaga.Sby. it was found that there were bankrupt debtors who proposed a second peace, as well as ratification of the peace by the panel of judges. Based on this, of course there is a discrepancy in the implementation of the second reconciliation based on the provisions of the laws and regulations in the PKPU process. The purpose of this study is to explore the judge's basis for implementing the second peace in the PKPU process and the legal consequences of implementing the second peace. In addition, it also aims to explore the legitimacy of the second peace. This study uses a type of normative juridical method, with a statutory regulation approach, a case approach, and a conceptual approach. The results of the study show that the basis of the judge used to implement the second reconciliation proposed by the bankrupt debtor is non-juridical in nature. The legitimacy of the second reconciliation proposed by the bankrupt debtor thus needs to be doubted, bearing in mind that the statutory provisions do not regulate this. Renewal of laws and regulations related to the second reconciliation by the bankrupt debtor thus becomes an urgency to be realized, in order to create legal certainty as well as justice for the parties.